CONTRACTOR SELECTION ASSESSMENT STRATEGY IN THE UPSTREAM OIL AND GAS INDUSTRY TOWARDS GREEN SUPPLY CHAIN MANAGEMENT - Prasetia, Fajar Tri; Shilul Imaroh, Tukhas (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Nowdays, the level of business competition in managing the upstream oil and gas industry is getting higher, therefore oil and gas companies need to improve their performance and optimize the existing resources in the company. This must also be considered in efforts to manage and save the environment, which is currently the main focus of governments and businesses to preserve the environment. In addition to internal improvements were made, improvements are also needed on the part of contractors/suppliers to support this. In this regard, this study was conducted to develop a strategy for conducting an assessment in the contractors selection/suppliers in the upstream oil and gas industry with the aim of implementing Green Supply Chain Management with the Analytic Hierarchy Process (AHP) method. This study maps the evaluation criteria and sub-criteria in the contractors selection and obtains the main criteria in the contractors selection for the upstream oil and gas industry towards Green Supply Chain Management. Results of the study obtain 6 criteria and 23 evaluation criteria in the contractors selection in the upstream oil and gas industry towards Green Supply Chain Management. The two most important criteria obtained are the Environmental criteria and the Health and Safety criteria, both of which have an assessment weight of more than 50% of the total assessment weight. The next criteria obtained are the Quality (Technical), Technical (Shipping), and Price (Quality) criteria, where these criteria are taken into account in the selection of contractors for the upstream oil and gas industry towards Green Supply Chain Management, so that the spirit of competition remains with the contractor and companies have many options contractor to achieve Green Supply Chain Management.